Oral ruxolitinib induces hair regrowth in patients with moderate-to-severe alopecia areata - Julian Mackay-Wiggan; Ali Jabbari; Nhan Nguyen; Jane E. Cerise; Charlotte Clark; Grace Ulerio; Megan Furniss; Roger Vaughan; Angela M. Christiano; Raphael Clynes (JCI Insight, 2016)
BACKGROUND. Alopecia areata (AA) is a common autoimmune disease with a lifetime risk of 1.7%; there are no FDA-approved treatments for AA. We previously identified a dominant IFN-γ transcriptional signature in cytotoxic T lymphocytes (CTLs) in human and mouse AA skin and showed that treatment with JAK inhibitors induced durable hair regrowth in mice by targeting this pathway. Here, we investigated the use of the oral JAK1/2 inhibitor ruxolitinib in the treatment of patients with moderate-to-severe AA. METHODS. We initiated an open-label clinical trial of 12 patients with moderate-to-severe AA, using oral ruxolitinib, 20 mg twice per day, for 3–6 months of treatment followed by 3 months follow-up off drug. The primary endpoint was the proportion of subjects with 50% or greater hair regrowth from baseline to end of treatment. RESULTS. Nine of twelve patients (75%) demonstrated a remarkable response to treatment, with average hair regrowth of 92% at the end of treatment. Safety parameters remained largely within normal limits, and no serious adverse effects were reported. Gene expression profiling revealed treatment-related downregulation of inflammatory markers, including signatures for CTLs and IFN response genes and upregulation of hair-specific markers. CONCLUSION. In this pilot study, 9 of 12 patients (75%) treated with ruxolitinib showed significant scalp hair regrowth and improvement of AA. Larger randomized controlled trials are needed to further assess the safety and efficacy of ruxolitinib in the treatment of AA. TRIAL REGISTRATION. Clinicaltrials.gov NCT01950780. FUNDING. Locks of Love Foundation, the Alopecia Areata Initiative, NIH/National Institute of Arthritis and Musculoskeletal and Skin Diseases (NIAMS), and the Irving Institute for Clinical and Translational Research/Columbia University Medical Center Clinical and Translational Science Award (CUMC CTSA).